Cross-Sectional Research on the Factors Influencing the Mental Health of Basketball Players - Moayad Fadhil Hassain; Murtada Sultan Al-Issa; Taha Al Hiali; Abdul Razzaq Jaber Al Majidi; Zaid Hilal Abed Alqiraishi; Ali Falah Mohamed; Hussam Abdali Abdulridui; Mohammad A. Harfouch; Maher Mohamed Al-Ameri; Mortada Kareem Sabi AlTalb, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The objective of this study was to fill the existing knowledge void and assess the effects of functional training, sports psychology, and team-building activities on the psychological well-being of basketball players. This study focuses on the mental health of players in Iraq, as there is limited existing literature on this topic. In addition, the study focused on the population of basketball players in Iraq, with a sample size of 200 Iraqi basketball players. Data was collected using random sampling, specifically from a five-point Likert scale questionnaire. The data collected for this research was analysed using R Packages in RStudio. A study revealed that functional training, sports psychology, and team building have a significant and positive effect on the mental well-being of basketball players in Iraq. This study filled the gaps in the existing literature by making a valuable theoretical contribution. The research findings are highly reliable for informing practical policymaking and implementation strategies aimed at improving the mental health of basketball players in Iraq.